2014
DOI: 10.4067/s0717-95022014000300017
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Curcumin Against Nicotine-induced Damage on Reproductive Parameters in Male Mice

Abstract: SUMMARY:Nicotine consumption can decrease fertility drive in males through inducing oxidative stress and DNA damage. The color of turmeric is because of a substance called curcumin for which some anti-oxidative and anti-inflammatory properties have been identified. In this study, various doses of curcumin (10, 30 and 60 mg/kg) and curcumin plus nicotine (10, 30 and 60 mg/kg) were administered intraperitoneally to male mice for 28 consequent days and reproductive parameters were determined. The results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 24 publications
2
52
0
3
Order By: Relevance
“…The abstracted cauda epididymides wer transferred into a Petri dish containing DMEM/F12 (Gibco-Cat.32500-05) and were incubated at 37°C , CO 2 (5 %) for 7 minutes (Jalili et al, 2014). Fifty ml of the culture medium containing semen liquid was removed and placed on glass slide, and sperm motility was evaluated by a light microscope with a magnification of 40× in ten vision fields based on WHO procedure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The abstracted cauda epididymides wer transferred into a Petri dish containing DMEM/F12 (Gibco-Cat.32500-05) and were incubated at 37°C , CO 2 (5 %) for 7 minutes (Jalili et al, 2014). Fifty ml of the culture medium containing semen liquid was removed and placed on glass slide, and sperm motility was evaluated by a light microscope with a magnification of 40× in ten vision fields based on WHO procedure.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown the existence of morphine receptors in sertoli and leydig cells of testis and have further addressed the involvement of inflammation and oxidation during male reproductive system exposure to morphine by producing NO and regulating inflammatory cascades (Jalili et al, 2016;Chehrei et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Once the photo was prepared, the number of cells was counted per 1 mm 2 area. On the slides, stained by means of Cresyl violet technique, the round cells without peak nose were considered as live cells 19 .…”
Section: Cresyl Violet Methodsmentioning
confidence: 99%
“…Nowadays, m edicinal plants hav e num erous applications and one of t he t arget tissues f or plant extrac ts is r eproductiv e organs s uc h as t estis and sperm paramet ers (Jalili et al, 2014) In t he herein s tud y, mic e co-administr at ed with c urc umin s howed ultrastr uct ural feat ures clos e to t hat of normal testic ular archit ect ure. Curc umin w as ass umed to increases the count and m otilit y of norm al sperms i n tr eat ed groups t hrough enhanci ng t he anti -oxid ant def ense of the body (V alko et al, 2005).…”
Section: Discussionmentioning
confidence: 99%